Endophilin-A coordinates priming and fusion of neurosecretory vesicles via intersectin - Sindhuja Gowrisankaran (Nature Portfolio, 2020)
Endophilins-A are conserved membrane-associated proteins required for endocytosis. Here, the authors report that endophilins-A also promote exocytosis of neurosecretory vesicles by coordinating priming and fusion through intersectin-1, independently of their roles in different types of endocytosis.